From Neopatrimonial Science to Consumption of Academic Degrees: The Case of Political Science in Ukraine - Osin, Vadym (My University, 2024)
This paper is devoted to the transformation of the practices of obtaining academic degrees in Ukraine by applicants from outside the Academy. My hypothesis is that neopatrimonial science, political regime, and credentialism have led to consumption of academic degrees in Ukraine. It is a socially and politically selective process, where the initial pattern is established by the reference groups of top officials. This pattern is subsequently copied and reproduced by lower ranks. It is related to (economically) favorable conditions contributing to the transfer of academic regalia from the category of luxury goods to objects of mass consumption. This process has its own specific features for different groups of applicants from outside the Academy, where the significant factors are the applicant’s position and its rank, regional structure of the political regime, and gender. The empirical basis of the work was: (a) career patterns of 642 former and current governors and/or heads of Regional Councils during 1992–2024; (b) 1,735 candidate (PhD) theses in political science defended during 1999–2024.
Keywords: neopatrimonial science; consumption; academic degrees; political science; Ukraine; gender